IMPLEMENTATION OF ENVIRONMENTAL ACCOUNTING IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) OF LAYER POULTRY FARMS: A CASE STUDY ON THE IMPACT OF ENVIRONMENTALLY FRIENDLY INITIATIVES ON THE PRODUCTION COST STRUCTURE - Hasnidar, Hasnidar; Hastuti; Made Ngurah Purnaman, Si; Irfandy Azis, Muh. (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to evaluate the implementation of environmental accounting (green accounting) through environmentally friendly initiatives that impact the production cost structure at Reban Lestari Poultry Farm, Kolaka. A qualitative descriptive approach was employed, emphasizing a deep understanding of the research object based on factual data obtained in the field. This approach is considered appropriate for examining the application of green accounting through a case study at the farm, with a focus on interpreting meaning rather than generalizing results. The data sources comprised both primary and secondary data, collected through in-depth interviews, direct observation, and documentation. The findings reveal that initiatives such as water sterilization, fly control, waste processing, and the use of energy-saving lamps contribute to increased overhead cost efficiency and support productivity. However, the application of green accounting in financial reporting remains limited, as evidenced by the incomplete financial statements only income statements are prepared, without balance sheets or accompanying notes thus failing to fully reflect the principles of environmental accounting.